Naród, gender, popkultura. Nacjonalistyczne konstrukcje płci i seksualności w popkulturowej odsłonie - Zamojska, Eva (Kultura-Społeczeństwo-Edukacja, 2019)
The paper is a short theoretical summary of relationships between the notions of nation, gender and sexuality in a nationalistic discourse. It is also an attempt at applying this knowledge for analyzing selected artifacts of pop culture. In the first part of the paper, theoretical and research findings on the constructs of gender and sexuality in a nationalistic discourse are presented. In the second part these findings are used for a discursive analysis of gender and sexuality constructs in selected songs / stage acts presented at the Eurovision Song Contest 2014 and a pastiche cover version of one of them.